Atypical Location of Lymphocytoma Cutis in a Child. Issue 5 (1st July 2013) - Amschler, Katharina; Schön, Michael P.; Mempel, Martin; Zutt, Markus
Abstract Lyme borreliosis is a common infectious disease that can affect myocardial muscle or the central nervous system if not treated at an early stage. Here we report a unique case of an atypical location of lymphocytoma cutis in a 3‐year‐old boy. Histologic and immunohistochemical analysis revealed the correct diagnosis.